First Report from Colombia of a Urinary Tract Infection Caused by Kluyvera ascorbata Exhibiting an AmpC Resistance Pattern: A Case Report - Esteban Artunduaga-Cañas; Sinthia Vidal-Cañas; Valentina Pérez-Garay; Johnny Valencia-Ibarguen; Diego Fernando Lopez-Muñoz; Yamil Liscano (Diseases)
Background: Urinary tract infections represent a significant healthcare burden, particularly among vulnerable patients with chronic comorbidities. In this case report, we describe a UTI caused by Kluyvera ascorbata exhibiting an AmpC resistance pattern in an 85-year-old male with stage IV chronic kidney disease and a history of ESBL-positive infection. Methods: A comprehensive diagnostic workup was performed, including clinical evaluation, laboratory tests (urinalysis, complete blood count, renal function tests), and microbiological cultures with antibiogram analysis using the MicroScan WalkAway (Beckman Coulter, Brea, United States) and VITEK2 Compact systems (bioMérieux, Marcy L’Étoile or Craponne, France). Results: The initial urine culture revealed a Gram-negative bacillus and subsequent identification confirmed K. ascorbata, which demonstrated resistance to ampicillin and cefazolin while remaining susceptible to meropenem. The patient received intravenous meropenem therapy for 10 days, resulting in clinical improvement and a subsequent negative urine culture. Conclusions: This case reports a complicated urinary tract infection caused by K. ascorbata with an AmpC resistance pattern, highlighting the importance of considering this infrequently reported pathogen and its resistance profile in vulnerable patients. Its multidrug-resistant profile underscores the necessity for vigilant antimicrobial stewardship and further research to develop standardized treatment protocols for managing infections caused by this organism.